Penyuluhan Inisiasi Menyusui Dini Di Kute Desa Kaya Pangur - Hasanalita Hasanalita (Fakultas Teknik Universitas Cenderawasih, 2022)
Early Breastfeeding Initiation (IMD) can prevent 22% of infant deaths in developing countries at the age of under 28 months, but if the first breastfeeding, when the baby is over two hours old and under the first 24 hours, it can prevent 16% of infant deaths under 28 day. Things that can affect the implementation of IMD, namely first, attitude and health workers. The results showed that the mother's perception of reduced milk production was caused by a lack of knowledge about the normal process of breastfeeding, but most mothers could overcome this if they received proper guidance from health workers. This community service was carried out in April 2022 in Kute, Kaya Pangur Village. The target of this activity is pregnant women, totaling 35 people. This counseling activity was carried out in the form of providing materials and leaflets about early initiation of breastfeeding